Evolving Tobacco Consumption in Sub-Saharan Africa - Araújo,Carla (2011)
Tobacco smoking is the single most important determinant of avoidable morbidity and mortality worldwide. In Sub-Saharan Africa smoking of manufactured cigarettes tends to be more frequent among urban dwellers while subjects living in rural areas are more often consumers of smokeless tobacco and hand-rolled cigarettes. The rural-to-urban migration is an important demographic phenomenon in Sub-Saharan Africa, and this shift will contribute to a faster transition through the stages of the tobacco epidemic than has been observed in higher-income countries. The widespread diffusion of cigarette smoking in developing settings will expectedly exacerbate worldwide health disparities between nations. The understanding of the patterns and dynamics of tobacco consumption in Sub-Saharan Africa is essential to develop and monitor locale-specific control strategies.